Efektivitas Hukum Kawasan Konservasi Perairan Maluku Utara: Studi Kasus Pulau Rao - Luhulima, Muhammad Fadly; Alwan, Sultan; Rosyidi, Irham (Wajah Hukum, 2024)
The use of prohibited fishing gear continues to pose a serious threat to aquatic ecosystems. The Regional Water Conservation Area Agency (Balai Kawasan Konservasi Perairan Daerah or KKPD) in North Maluku plays a crucial role in educating the public on responsible fishing practices for the sustainability of the region. However, insufficient socialization and monitoring in the conservation area of Pulau Mare have led to illegal fishing activities that harm the ecosystem. Lack of transparency in information regarding the performance of the KKPD becomes a challenge, leaving the community unaware of the progress in surveillance, rehabilitation, and utilization by the agency. This research analyzes the legal effectiveness of water conservation area management in North Maluku Province, focusing on the Pulau Rao-Tanjung Dehegila Conservation Area. The research employs a juridical-empirical method with primary data obtained through interviews and secondary data from literature studies. Ministerial Decree No. 67/KEPMEN-KP/2020 and Minister of Marine Affairs and Fisheries Regulation No. 31/PERMEN-KP/2020 mandate proper management. However, the implementation of these regulations has yet to be effective. In conclusion, water conservation area management in North Maluku requires increased socialization to raise awareness and garner public support for established programs. Further efforts are needed to ensure the effectiveness of these programs.